Paediatric Patients-Based Case-Control Analysis: The Association Between Serum Vitamin D Levels And Febrile Seizures - Masood, Shaheen; Farrukh, Riffat; Naseer, Amber; Nasir, Farhina; Shakoor, Ibrahim; Iqbal, Syed Arif (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the association between serum vitamin D levels and febrile seizures in the paediatric patients. Study Design: Case-Control Study. Place and Duration of Study: Abbasi Shaheed Hospital, Karachi Pakistan, from Mar 2020 to Mar 2021. Methodology: The study included all pyrexia paediatric patients, both with and without febrile seizures, as cases and controls. Children aged below six months or older than 60 months, with a previous history of afebrile seizures, diagnosed with central nervous system infection, dehydration, or electrolyte disturbance, were excluded from the study. Serum vitamin D levels and other demographic data were documented. Results: The study included 86 cases and controls. The mean age of cases was 28.07±16.47, and the controls were 26.38±15.72 months. The rate of vitamin D insufficiency was three times more likely in cases compared to controls, i.e. [OR, 95% CI: 3.95 (2.084—7.489)] with p=0.0001. Conclusion: Vitamin D deficiency is substantially more likely in the case than in the control group. As a result, children with febrile seizures should have their serum vitamin D levels tested.